Determinants of Corporate Financial Fraud: A Synthesis - Dewi Nur Maulidiyah; Puji Harto (Journal of Management and Entrepreneurship Research, 2024)
Objective: Corporate fraud has consistently been a subject of interest and remains an engaging topic of discussion. This paper aims to provide an understanding of the determining factors of corporate financial fraud and offer recommendations for potential variables that can be further analyzed. Research Design & Methods: This paper reviews empirical studies from the last 10 years (2013-2023) published in the ScienceDirect.com database. A total of 31 papers were analyzed. Findings: 132 determining factors were identified as influencing corporate financial fraud. The most frequently investigated factors are financial ratios. Meanwhile, recent studies have increasingly linked financial fraud to board characteristics and external corporate factors. Overall, corporate financial fraud is driven by two key sources: internal and external factors, encompassing a variety of aspects such as economic, social, and political influences. Contribution & Value Added: This paper provides valuable insights for developing an effective fraud prevention and detection model for corporations.